THE USE OF AUDIO VISUAL AS MEDIA IN ENHANCING STUDENTSâ LISTENING SKILL - Rosdiana, Rosdiana (STKIP Bina Bangsa Getsempena Banda Aceh, 2018)
AbstractListening is a basic ability required in mastering English. The purpose of this article is to describe the utilization of audio visual media in improving listening skills of students majoring in STKIP Language BBG Banda Aceh. The main purpose of this research is 1) to know the application of learning development of audio-visual media in improving listening ability of first year English students ofÂ STKIP BBBG. 2) to know the increasing of listening ability of English student of second year students of STKIP BBBG after getting learning using audio visual media. This research is quantitative study. To achieve these objectives, purposive sampling is used which is focused on the first year student students semester II are taken as the subject of this research. Regarding the data analysis, mean, percentage and t-test scores for the dependent sample were employed. The result indicated that 1) the studentsâ English listening comprehension ability increased significantly after learning with videos and 2) students had positive attitudes towards using videos in teaching listening skills.Â Keywords: Audio Visual Media, Listening